The Influence of iSpring Media Based on Computational Chemistry in the Cooperative Learning Model on Learning Outcomes in the Topic of Thermochemistry for Grade XI High School Students - Putri Nur Afiananda; Ervina Aulia Hrp; Asep Wahyu Nugraha (Universitas Lampung, 2025)
The Influence of iSpring Media Based on Computational Chemistry in the Cooperative Learning Model on Learning Outcomes in the Subject of Thermochemistry Class XI SMA. This study aims to determine the influence of the use of ispring media based on computational chemistry calculations on learning outcomes and student motivation in the subject of thermochemistry. This study was conducted at SMA Negeri 1 Pegajahan, Pegajahan District, Serdang Bedagai Regency. The population in this study were all students of class XI at SMA Negeri 1 Pegajahan, while the sample used was students of class XI6 as the experimental class and class XI1 as the control class. The instruments used in this study were test instruments in the form of multiple-choice objective tests to see student learning outcomes obtained through posttests and questionnaires in the form of statements to see student learning motivation. The results of the study showed the influence of the use of ispring media based on computational chemistry calculations in the TGT type cooperative learning model on learning outcomes and student motivation in the subject of thermochemistry. This can be seen from the results of the posttest hypothesis test using the t - test. The relationship between motivation and student learning outcomes shows that the correlation is 0.917 (very high correlation).